The Effect of Digital Media Information Access on Understanding Reproductive Health Intervention Studies in Students - Eva Mulyani S; Nurhayati Nurhayati; Nursapia Harahap; Rapotan Hasibuan (Jurnal Ners, 2026)
Limited access to accurate reproductive health information may increase adolescents' vulnerability to reproductive health problems. This study aimed to evaluate the effectiveness of digital media–based reproductive health education in improving digital information access and reproductive health knowledge among female students at Darul Iman Islamic Boarding School, Southeast Aceh. A quantitative one-group pretest–posttest study was conducted among 119 participants selected using total sampling. The mean score for digital information access score increased from 41.85 ± 7.54 (median = 41; 95% CI: 40.65–43.30) to 47.64 ± 6.79 (median = 47; 95% CI: 46.50–48.89). Similarly, the mean reproductive health knowledge increased from 6.06 ± 4.39 (median = 5; 95% CI: 5.30–6.87) to 15.97 ± 4.11 (median = 16; 95% CI: 15.23–16.72). Wilcoxon Signed-Rank Test results showed significant improvements in information access (Z = −9.303, p < 0.001, r = 0.853) and reproductive health knowledge (Z = −9.389, p < 0.001, r = 0.861). Digital media–based reproductive health education effectively improved access to reproductive health information and reproductive health knowledge among female Islamic boarding school students.